Le Petit Chaperon Rouge dans le bois de New York - Alice Brière-Haquet (Strenae)
There is, on one hand, Little Red Riding Hood, a symbol of the past with its fireside vigils, while on the other there is New York, a true representation of Western modernity with its frenetic rhythms. Two incompatible worlds? Three works prove it isn’t so... They include the picture books Le Loup de la 135e avenue by Rebecca Dautremer and Arthur Lebœuf, the Spanish novel Caperucita en Manhattan by Carmen Martín Gaite, and the comic strip by American Bill Willingham: Fables. Three perspectives with different origins and audiences that align in their desire to merge real space and imaginary worlds, offering a new type of initiation, both to the character as well as the reader.